SOSIODEMOGRAFI DENGAN PERILAKU PENCEGAHAN STROKE PADA KLIEN HIPERTENSI - I Ketut Gama (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2018)
Hypertension is defined where the systolic pressure is above 140 mmHg and the diastolic is above 90 mmHg. The behavior of stroke prevention among others by applying a healthy lifestyle. The purpose of this research is to analyze sosiodemography relationship with behavior of stroke prevention on hypertension client. If used cross sectional research design. The number of samples in this study 109 samples selected by non-probability sampling method with purposive sampling. This research has been conducted at UPT Kesmas Kuta Utara Badung Regency from second week of March 2017 until second week of April 2017. This research shows of respondent are non productive age (62,5%), female (62,4% ), high education(67%), does not work (56%), and good prevention behavior (67%). The result of this research is tested by statistical test of Multiple Logistic Regression, p value = 0,026 for age, p value = 0,030 for gender, p value = 0,000 for education, and p value = 0,039 for job. OR = 8,028 for age, OR = 5,827 for gender, OR = 9,742 for education, and OR = 5,601 for job. The conclusions shows that there is a significant relationship between sociodemography with stroke prevention behavior at UPT Kesmas Kuta Utara.